L. plantarum, L. salivarius, and L. lactis attenuate Th2 responses and increase Treg frequencies in healthy mice in a strain dependent manner. - Maaike J Smelt (PLoS ONE, 2012)
Many studies on probiotics are aimed at restoring immune homeostasis in patients to prevent disease recurrence or reduce immune-mediated pathology. Of equal interest is the use of probiotics in sub-clinical situations, which are characterized by reduced immune function or low-grade inflammation, with an increased risk of infection or disease as a consequence. Most mechanistic studies focus on the use of probiotics in experimental disease models, which may not be informative for these sub-clinical conditions. To gain better understanding of the effects in the healthy situation, we investigated the immunomodulatory effects of two Lactobacillus probiotic strains, i.e. L. plantarum WCFS1 and L. salivarius UCC118, and a non-probiotic lactococcus strain, i.e. L. lactis MG1363, in healthy mice. We studied the effect of these bacteria on the systemic adaptive immune system after 5 days of administration. Only L. plantarum induced an increase in regulatory CD103(+) DC and regulatory T cell frequencies in the spleen. However, all three bacterial strains, including L. lactis, reduced specific splenic T helper cell cytokine responses after ex vivo restimulation. The effect on IFN-γ, IL5, IL10, and IL17 production by CD4(+) and CD8(+) T cells was dependent on the strain administered. A shared observation was that all three bacterial strains reduced T helper 2 cell frequencies. We demonstrate that systemic immunomodulation is not only observed after treatment with probiotic organisms, but also after treatment with non-probiotic bacteria. Our data demonstrate that in healthy mice, lactobacilli can balance T cell immunity in favor of a more regulatory status, via both regulatory T cell dependent and independent mechanisms in a strain dependent manner.